Region based lossless compression for digital images using entropy coding - Vamsikrishna, Mangalapalli; Sudhakar, Oggi; Bugge, Bhagya Prasad; Kumar, Asileti Suneel; Thankachan, Blessy; Subrahmanyam, K.B.V.S.R.; Deepthi, Natha; Mande, Praveen (Institute of Advanced Engineering and Science, 2025)
Image compression is a method for reducing video and image storage space. Moreover, enhancing the performance of the transmission and storage processes is important. The region based coding technique is important for compressing and sending medical images. In the medical field, lossless compression can help telemedicine applications achieve high efficiency. It affects image quality and takes a long time to encode. As a result, this study proposes region-based lossless compression for digital images using entropy coding. The best performance is achieved by segmenting these areas. In this case, an integer wavelet transform (IWT) is utilized after the ROI of the image was manually generated. The IWT compression method is helpful for reversibly reconstructing the original image to the required quality. For enhancing the quality of compression, entropy coding is utilized. By passing images of varying sizes and formats, various quantitative metrics can be determined. The simulation results demonstrate that the region based lossless compression technique utilizing range blocks and iterations resulted in reduced encoding time and improved quality.